How Collective Participation Impacts Social Identity: A Longitudinal Study from India. Issue 3 (26th March 2015) - Khan, Sammyh S.; Hopkins, Nick; Reicher, Stephen; Tewari, Shruti; Srinivasan, Narayanan; Stevenson, Clifford
Abstract : A key issue for political psychology concerns the processes whereby people come to invest psychologically in socially and politically significant group identities. Since Durkheim, it has been assumed that participation in group‐relevant collective events increases one's investment in such group identities. However, little empirical research explicitly addresses this or the processes involved. We investigated these issues in a longitudinal questionnaire study conducted at one of the world's largest collective events—a month‐long Hindu festival in north India (the Magh Mela ). Data gathered from pilgrims and comparable others who did not attend the event show that one month after the event, those who had participated (but not the controls) exhibited heightened social identification as a Hindu and increased frequency of prayer rituals. Data gathered from pilgrims during the festival predicted these outcomes. Specifically, perceptions of sharing a common identity with other pilgrims and of being able to enact one's social identity in this event helped predict changes in participants' identification and behavior. The wider significance of these data for political psychology is discussed.